REFLECTIONS OF THE GENERAL DATA PROTECTION LAW IN THE HOSPITAL MEDICAL SECTOR (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This research addresses how the abyssal thinking, present in the work of Boaventura de Sousa Santos, reverberates in society, specifically in the health sector. The individual who is on the "other side of the line" is usually placed on a level of inferiority and invisibility, which leads to social inequality. The study demonstrates how such inequality leads individuals to not have satisfactory access to health. However, the research does not merely deal with the impossibility of access to health as a social service guaranteed by the State, but also with the state of health as an individual. Throughout the study, it will be proved that social inequality, the result of abyssal thinking, leads individuals "on the other side of the line" to have greater chances of not being able to maintain their health. It will thus be possible to observe the urgent need to establish post-abyssal thinking, which values the equalization of individuals, their practices and cultures, on both sides of the line.